Integration of Character Value Models in Senior High School - Fatimah Azis; Rahmat Nur; Ananda Setiawan (STAI Hubbulwathan Duri, 2023)
Prevention of violations of character values is essential to note. This is an effort to prevent students from committing acts of violating the character values adopted by the community. The instilling of character values in schools has also not had a significant impact. It is proven that there are still students who violate the values and norms in society. This needs to be studied more deeply to find theoretical gaps regarding cultivating character values in schools. This study aims to find and prove the value model of character education in schools. The substance of the problem in this study is the tendency of bad student behaviour, so it requires a more complex and structured model of character values. This study uses a mixed method (qualitative and quantitative) to find ways to integrate character models in senior high school. This research was conducted at a state senior high school in Banjarmasin. There are 36 respondents (32 students and 4 teachers) in this research. The research instrument is the researcher himself as main instrument, a quantitative instrument using a questionnaire. Informant selection by purposive sampling for qualitative data, random sampling for quantitative data, and data collection via interview, observation, questionnaire, and documentation. Reducing, displaying, and verifying data are the first steps in the data analysis process. The results of research on the development of an integrated character value model have been developed at senior high school with the integration of the character value model of knowing, feeling and action in reducing the violation of character values in schools. The pedagogic implication of this research is that school leaders can use character models in an effort to prevent students from violating values and norms.